The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/prs.0000000000005664
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Symptomatic Neuroma: Anatomic Distribution and Predictors of Secondary Surgery

Abstract: Background: Neuromas are caused by irregular and disorganized regeneration following nerve injury. Many surgical techniques have been described to address neuroma with varying success. The aim of this study was to evaluate predictive factors for secondary surgery after initial surgical intervention for symptomatic neuroma along with a description of the anatomical distribution of surgically treated symptomatic neuromas. Methods: Five hundred ninety-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 53 publications
3
27
0
Order By: Relevance
“…14 Also, Wolvetang et al found lower rates of secondary neuroma surgery in patients undergoing neurorrhaphy with or without nerve graft compared with those undergoing implantation techniques. 15 Although no specific technique proved to be clearly superior, our data demonstrated that surgical intervention should be considered in the treatment algorithm for patients suffering from painful neuroma refractory to conservative management.…”
Section: Discussionmentioning
confidence: 76%
“…14 Also, Wolvetang et al found lower rates of secondary neuroma surgery in patients undergoing neurorrhaphy with or without nerve graft compared with those undergoing implantation techniques. 15 Although no specific technique proved to be clearly superior, our data demonstrated that surgical intervention should be considered in the treatment algorithm for patients suffering from painful neuroma refractory to conservative management.…”
Section: Discussionmentioning
confidence: 76%
“…30 Although these data are limited, symptomatic neuromas reduce patient quality of life, increase the risk of developing an opioid misuse disorder, may lead to multiple additional operations, and lead to donor-site allodynia and other complications such as infection. 59,[61][62][63][64][65][66][67] Finally, the procedure cost analysis demonstrated that overall allograft costs are 825e lower than autograft costs the inpatient setting and comparable in the outpatient setting. This suggests that allograft repair may achieve similar outcomes at similar or lower costs as compared with autograft repair.…”
Section: Cost Analysismentioning
confidence: 95%
“…41 In accordance with other studies the surgical intervention remains recommended only for patients with painful neuromas who are not responsive to medical or other treatments. 42,43 It seems that the surgical procedure could at least partially dissolve the pain triggering mechanisms of the old scar neuromas, whereas the new scar neuromas created by this surgical procedure may follow new and different rules. This could support the suspicion that operating on a pain condition with a wrong assumption of its origin could still solve the pain problem at least partially.…”
Section: Therapeutic Optionsmentioning
confidence: 99%